2015
DOI: 10.5468/ogs.2015.58.4.268
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of three-dimensional reconstruction and automated measurement of fetal long bones using 5D Long Bone

Abstract: ObjectiveTo evaluate the feasibility of five-dimensional Long Bone (5D LB), a new technique that automatically archives, reconstructs images, and measures lengths of fetal long bones, to assess whether the direction of volume sweep influences fetal long bone measurements in three-dimensional (3D) ultrasound and 5D LB, and to compare measurements of fetal long bone lengths obtained with 5D LB and those obtained with conventional two-dimensional (2D) and manual 3D techniques.MethodsThis prospective study include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…In an effort to overcome this drawback, long bone automated detection system by 5D was introduced to create an operator independent, quick and efficient method for accurate estimation of fetal birth weight. In the current trial, this fully automated system revealed absolute birth weight estimation error of 0.95% which is comparable to the previous work of Hurr et al, who reported an overall error rate of 5.4% in a larger sample [8].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In an effort to overcome this drawback, long bone automated detection system by 5D was introduced to create an operator independent, quick and efficient method for accurate estimation of fetal birth weight. In the current trial, this fully automated system revealed absolute birth weight estimation error of 0.95% which is comparable to the previous work of Hurr et al, who reported an overall error rate of 5.4% in a larger sample [8].…”
Section: Discussionsupporting
confidence: 88%
“…Despite the obvious superiority of 3D ultrasound in estimation of fetal birth weight, the technique is still operator dependent and requires a learning curve for proper acquisition and manipulation of volume data [8]. In an effort to overcome this drawback, long bone automated detection system by 5D was introduced to create an operator independent, quick and efficient method for accurate estimation of fetal birth weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractional limb volume measurements were calculated with a WS80A ultrasound system (5D Limb Vol; Samsung Medison) . Each end of the limb diaphysis was automatically detected with a previously described software tool (5D Long Bone) . The partial limb volume was automatically subdivided into 5 equidistant cross‐sectional image slices that were centered along the midarm or midthigh.…”
Section: Methodsmentioning
confidence: 99%
“…7,15 Each end of the limb diaphysis was automatically detected with a previously described software tool (5D Long Bone). 16 The partial limb volume was automatically subdivided into 5 equidistant cross-sectional image slices that were centered along the midarm or midthigh. An image transformation procedure required the examiner to identify the major and minor axis diameters of each limb cross section and to mark the location of the bony diaphysis.…”
Section: Three-dimensional Volume Data Analysismentioning
confidence: 99%